How Does the Agent’s Perceived Intentions Change Consumers Response to the Humorous (Disparagement Humor) Advertisement in Morocco? - Nejjar, Ichraq (2012)
Humorous advertisements are widely used in Morocco. Disparagement humour in particular is gaining popularity within Moroccan advertisers. However, little research has been done in order to assess consumer’s feelings and opinions towards these advertisements. This research will therefore examine female Moroccan’s sentiments and opinions towards disparagement advertisements by employing the persuasion knowledge model as a framework, and specifically focusing on the impact that the perceived advertiser’s manipulative intent has on consumers’ reaction towards the advertisement. The study focuses on fifteen interviews of Moroccan women between the age of 21 and 28. The results demonstrate that disparagement humour is perceived to be funny when it is quick, clear and easy to understand. Most participants also claim that it is an innovative way that will most likely succeed at capturing the audience’s attention. Disparagement humour is also appreciated when the subject disparaged is not affiliated with the audience in any way. However, it is perceived to be unacceptable if it attacks a subject of major importance to customers such as religion and race. Disparagement humour is also perceived to be hurtful to the population the advertisement is mocking; connotations such as humiliation and ridicule frequently occur during the interviews. Therefore most participants perceive disparagement humour to be risky but affirm that their perception about the brand will not change if it is a highly recognized brand that is well established in the market. On the other hand, they assert that it is extremely unadvisable for a new brand still establishing itself and creating its brand image. Most participants perceive advertiser’s intentions to be manipulative but affirm that the manipulative intent does not have an effect on their perception on the brand nor on their purchase intentions. Participants assert that nowadays all advertisements are manipulative and that they rely mostly on previous experience and product quality to make their choices rather than their liking or disliking of an advertisement.